Pembuatan Aplikasi Jasa Penitipan Pembelian Barang Berbasis Android - Derryl Fharizal; Henri Septanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Technology can shorten the time of purchase of goods in order to get the maximum time in carrying out activities. Pre-order goods purchasing service application for help people who do not have much time to buy goods and can not be present at certain events to buy goods. This application is based on Android and to search for providers of goods storage services through the posts made. This application helps to bring together service users and service providers to pre-order/request goods. The application is created using PHP, XML, Java, and MySQL programming languages. The method used is the Rational Unified Process (RUP) with the Unified Modeling Language (UML) system modeling. The results of this study are Android-based goods purchasing services.